Comparative UV-Spectroscopic and Chemical estimations of Atropine Alkaloid present in Datura stramonium found in Saudi Arabia (Journal of Advances and Scholarly Researches in Allied Education, 2024)
Aim: To find out the concentration of Atropine alkaloid in Datura stramonium of Saudi Arabian Region and to develop a new method of the Atropine estimation.Methods: The presence of Atropine in the alcoholic extract of leaves of Datura stramonium was known by Qualitative TLC profile. Quantitative estimation of Atropine in the extract was done with UV Spectrophotometric Method (new proposed method for determination of Atropine in plant extract) and Titrimetric Method (Pharmacopoeial method) and results were compared.Results: Qualitative (TLC) Result showing the presence of Atropine in the Datura stramonium extract. After applying the calculations the concentration of Atropine was found to be 0.3% (w/w). Since the both quantitative results were comparable and the values of the results were approximately equal supporting the validation of New Method.Conclusion: The Saudi Arabian geographical variety of Datura stramonium contains the Atropine Alkaloid as 0.3% (w/w) which is close to the reported value. The new method for the quantitative estimation of Atropine i.e. UV spectroscopic method was developed successfully.